2015
DOI: 10.1088/0029-5515/55/3/033016
|View full text |Cite
|
Sign up to set email alerts
|

Electron cyclotron resonance heating beam broadening in the edge turbulent plasma of fusion machines

Abstract: Two analytical models for the ordinary mode propagating through a turbulent inhomogeneous edge plasma layer are developed based on the eikonal perturbation method and weak turbulence theory approach. Simple analytical expression for a diffusion-like angular beam width variation is obtained by both methods in the case of long scale density perturbations. The predictions for the spatial beam width are benchmarked against timeaveraged results coming from the 2D Maxwell's equations solver for different turbulence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 21 publications
3
40
0
Order By: Relevance
“…The influence of edge plasma density fluctuations on injected microwaves has been studied with geometrical-optics tools in the 1980s in a fusion-relevant context when high-power microwave sources became available [11][12][13]. The topic has been brought back into focus by Tsironis in 2009 [14] which triggered a significant follow-up research looking into this problem using different techniques [15][16][17][18][19][20][21][22]. As a common agreement one can state that (a) substantial broadening of microwave beams due to edge plasma density perturbations is expected, (b) the situation in medium-sized tokamaks differs from large-scale tokamaks like ITER (due to differences in microwave frequency, size of turbulent structures, and propagation length), (c) further and more detailed studies with a minimum of simplifying assumptions are needed for the ITER scenarios which cannot be explored experimentally in today's tokamaks, and (d) the various numerical tools should be cross-benchmarked.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of edge plasma density fluctuations on injected microwaves has been studied with geometrical-optics tools in the 1980s in a fusion-relevant context when high-power microwave sources became available [11][12][13]. The topic has been brought back into focus by Tsironis in 2009 [14] which triggered a significant follow-up research looking into this problem using different techniques [15][16][17][18][19][20][21][22]. As a common agreement one can state that (a) substantial broadening of microwave beams due to edge plasma density perturbations is expected, (b) the situation in medium-sized tokamaks differs from large-scale tokamaks like ITER (due to differences in microwave frequency, size of turbulent structures, and propagation length), (c) further and more detailed studies with a minimum of simplifying assumptions are needed for the ITER scenarios which cannot be explored experimentally in today's tokamaks, and (d) the various numerical tools should be cross-benchmarked.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the electron density fluctuations near the plasma edge, or along the path of the RF-waves, might lead to a broadening of the current deposition as well as a fluctuating power deposition profile Tsironis et al (2009) ;Peysson et al (2011); Decker, J. et al (2012). In ITER, the local micro-turbulence impact should be negligible and will not significantly increase the current width Casson et al (2015), but effects of edge turbulence on wave propagation might enlarge considerably the EC deposition, up to a factor 2 Tsironis et al (2009) ;Peysson et al (2011); Decker, J. et al (2012); Sysoeva et al (2015). As these effects are difficult to control, it is necessary to design control strategies that are able to overcome them.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to difficulties in the interpretation of diagnostic signals [16] and to a potential loss of efficiency in EC heating and mode stabilization, as suggested by numerical [16,17] and analytical [18] studies. Recently, concerns over the possible broadening effect of blobs on EC beams were raised for ITER [19,20]. The precise amount of EC-beam broadening may strongly depend on the characteristics of the turbulent structures [21] and could reach more than a factor of 2 [17], complicating the tearing mode stabilization in ITER [19,22] with the present EC plant design.…”
mentioning
confidence: 99%